A study of tool wear prediction of cylindrical grinding wheel - Mohd Nazmi, Mohd Nordin (2010)
This project was about a study of tool wear prediction of cylindrical grinding wheel. the aim of this work is to monitor dynamic interaction that cause tool wear to occur on the cylindrical grinding wheel and create a prediction of tool wear on cylindrical grinding wheel.